Development of the Two Heterogeneous Photosystem II Units in Etiolated Bean Leaves - Melis, Anastasios (1977)
The development of the photosystem II units in relation to the heterogeneity of their photochemical centers was studied in etiolated bean leaves (Phaseolus vulgaris var. red kidney) greened under continuous or intermittent light. The study was done in order to see whether grana are the loci of the units with the efficient photosystem II activity (α units), while the stroma thylakoids are the loci of the units with the less efficient photosystem II activity (β units), as it has been proposed. In addition, the interrelations between α and β centers have been investigated. It was found that the α and the β centers of photosystem II were present in the first photosynthetic membranes irrespective of the mode of greening of the leaves. The magnitude of their respective photochemical rate constants, K′(α) and K(β), increased with time in continuous light and it reached the steady-state values of the mature chloroplasts within 16 hours, while in intermittent light it remained smaller. The differentiation of the system II units in α and β centers containing units is more evident under conditions of intermittent illumination, i.e. when the rate of chlorophyll biosynthesis is the limiting step for chloroplast development. It is concluded that the heterogeneity of the photochemical centers in system II is an endogenous property of the chloroplast lamellae. The α centers and the β centers develop independently of each other from the beginning of the light-induced greening. They do not share the same pigment beds. The presence of grana, chlorophyll b, and the chlorophyll-protein complex II is not a prerequisite for the formation or development of the α centers. The formation of these centers precedes grana formation in greening plastids.